Pengaruh Pendekatan Culturally Responsive Teaching (CRT) Terhadap Motivasi Belajar Matematika Siswa Kelas VIII-B SMP Negeri 2 Palu - Lamalaka, Safira Seftianingsih; Baharuddin; Rosdiana (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to examine the effect of implementing Culturally Responsive Teaching (CRT) on the mathematics learning motivation of eighth-grade students at SMP Negeri 2 Palu. The problem stems from students’ low motivation, which leads to difficulties in understanding concepts, weak problem-solving skills, and low learning outcomes. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, carried out in two cycles with 32 students as the subjects. Data were collected through a Likert-scale motivation questionnaire and classroom observation. The results showed an increase in learning motivation from 61% (moderate category) in the pre-cycle, to 66% (moderate category) in the first cycle, and 76% (high category) in the second cycle. Improvements were evident in several indicators, including the desire to succeed, learning drive, future aspirations, recognition in learning, engaging learning activities, and a supportive classroom environment. Thus, the implementation of CRT was proven to enhance students’ mathematics learning motivation through contextual, meaningful, and culturally relevant instruction, while also highlighting the importance of integrating students’ cultural backgrounds and real-life experiences as strategies to foster motivation and active participation in learning.